2023
DOI: 10.1021/acsapm.3c00625
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-alkyl-2-oxazoline)-Based Copolymer Library with a Thermoresponsive Behavior in Dodecane

Abstract: Poly­(2-oxazoline)­s are an emerging class of polymers due to their high versatility and hence have proven to be beneficial in numerous applications. The extensive study and interest in this polymer class is due to their great synthetic flexibility and good biocompatibility, resulting in the synthesis of extremely functional material, particularly advantageous in biomedical applications. Although the thermoresponsive behavior of POx has been extensively studied in aqueous media, there is only limited literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…38 Propargyl tosylate (PropTos) was selected as the initiator to introduce alkyne functionality at the α-end of the chain for post-polymerization modification using thiol–yne click chemistry. In a recent study from our group, 39 we found that using PropTos resulted in the complete and efficient initiation of EtOx at a lower temperature of 100 °C with no sign of non-linear first order kinetics which is indicative of slow initiation. The synthetic procedures of all oligomers is outlined in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…38 Propargyl tosylate (PropTos) was selected as the initiator to introduce alkyne functionality at the α-end of the chain for post-polymerization modification using thiol–yne click chemistry. In a recent study from our group, 39 we found that using PropTos resulted in the complete and efficient initiation of EtOx at a lower temperature of 100 °C with no sign of non-linear first order kinetics which is indicative of slow initiation. The synthetic procedures of all oligomers is outlined in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Recently, a study found that poly­(2-oxazoline)­s (POxs) are a promising short-term dispersant of CB in dodecane . POx is a class of polymers that have been gaining emerging attention in both industrial and biological applications due to their unparalleled synthetic versality. Recent studies have consistently showcased their benefits in biological applications , but their potential in other uses is rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers such as PMeOx and PMeOz, for example, are both known to be fully water-soluble up to 100 °C, thus would be considered equally hydrophilic via turbidimetry assessment. 30,31 Assessment of the hydrophilicity of individual PCIEs has been largely limited in the literature to the measurement of cloud point temperature ( T cp ), 22,30,31,43 contact angle (both water and multi-solution) 44–48 and surface energy, 45,49 and, more recently, high-performance liquid chromatography (HPLC) retention time. 10,50–53 While important properties to consider, some of these techniques have notable limitations.…”
Section: Introductionmentioning
confidence: 99%